(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background – Sweet potato (Ipomoea batatas) starch has been reported for its potential as a directly compressible and sustained-release polymer in its native and modified forms. Chemical modification by crosslinking with urea and borax to form starch urea-borate will enhance its drug release-retarding properties. Objective – To design starch-urea-borate (SUB) polymer using sweet potato starch to produce a new, affordable biodegradable polymer, and carry out preliminary characterization of the polymer. Method – Native starch was extracted from sweet potato tubers and crosslinked with urea and borax to form starch-urea borate (SUB) polymer. The native and modified starches were characterized for morphology (SEM), FT-IR, DSC, pH, densities, swelling, flow properties and viscosity. Results – Modification yielded 96.66% w/w of SUB and disrupted the granular structure of the native starch, producing significantly larger (p<0.01) granules with irregular shapes. FTIR spectrum revealed a peak at 3369.05 cm-1 due to –NH2 confirming the presence of a secondary amide resulting from the polymerization reaction between urea and starch in the presence of borate. A shift in the peak of DSC endotherm was observed for SUB. Modification yielded lower particle density but higher bulk and tapped densities. The swelling index increased significantly (p<0.01). Hausner’s ratio (1.06± 0.00), Carr’s index (6.33± 0.01%) and angle of repose (26.14±1.15º) showed good flow but reduction in compressibility of SUB. Viscosity revealed shear thickening or dilatant behaviour. Conclusion- The material and physicochemical properties of SUB polymer showed its potential for application in drug delivery systems, possibly as a release retarding polymer.